Research methods in language policy and planning : a practical guide - Hult, Francis M.; Johnson, David Cassels, 1974- (Chichester, West Sussex : Wiley-Blackwell, 2015)
"This book is the first volume that is exclusively devoted to research methods in language policy and planning"--
Part II Methodological Approaches to Language Planning and Policy ResearchChapter 7 Exploring Language Problems through Q-Sorting; Introduction; Developing Research Questions; Choosing Contexts; Methods for Data Collection and Analysis; Case Study; References; Further Reading; Chapter 8 Ethnography in Language Planning and Policy Research; Introduction; Developing (Good) Research Questions; Choosing Contexts; Methods for Data Collection and Analysis; Case Study: The Native Language Shift and Retention Study; Concluding Thoughts; References; Further Reading
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Language policy -- Research -- Methodology; Language planning -- Research -- Methodology; Language and languages -- Research -- Methodology; LANGUAGE ARTS & DISCIPLINES / Linguistics / General; Language and languages -- Research -- Methodology; Language planning -- Research -- Methodology; Language policy -- Research -- Methodology; POLITICAL SCIENCE / Public Policy / Cultural Policy; SOCIAL SCIENCE / Anthropology / Cultural; SOCIAL SCIENCE / Popular Culture; Electronic books